EVALUATION OF COMBINING ABILITY OF PARTHENOCARPIC GENOECIOUS AND MONOECIOUS LINES FOR PRODUCTIVITY OF PICKLING CUCUMBERS AND STANDARD FRUITS - Truong Giang Nguyen; A. A. Ushanov; G. F. Monakhos (Овощи России)
The results of a study of the genetic control and evaluation of combining ability for productivity of pickling cucumbers and standard fruits of 20 cucumber lines obtained after crossing 10 parthenocarpic gynoecious and 10 monoecious lines resistant to downy mildew are presented in the article. The cucumber lines with the high combining ability were identified. In the future, these lines will be used in breeding programs.